Angelomorphic pneumatology : Clement of Alexandria and other early Christian witnesses - Bucur, Bogdan Gabriel (Supplements to Vigiliae Christianae ;, 2009)
This monograph on Clement of Alexandria's pneumatology supplemented by studies of Revelation, Shepherd of Hermas, Justin Martyr, and Aphrahat, shows that the complex theological articulation of angelomorphic pneumatology, binitarianism, and spirit christology constitutes a relatively widespread phenomenon in early Christianity.